Development of Augmented Reality-Based Learning Media for Solid Geometry for Elementary School Students - Saputra, Ricky Aditya; Alfarizi, Muhammad; Saputri, Fiqih Hana; Ferawati, Ferawati (Politeknik Ganesha Medan, 2025)
AR-based media is expected to create a more interactive and engaging learning experience, enhance students’ understanding, and motivate them to learn independently and actively in the digital era. The data collection stages applied include testing, observations, and the distribution of questionnaires. The development of this learning media follows the MDLC model, which aims to design improvements to the existing system. The results of the blackbox testing, the